Dramatic decrease in left ventricular mass with octreotide treatment in a patient with primary hypertrophic cardiomyopathy - Gunal, A.I.; Eren, O.; Isik, A.; Elmaci, H.C.; Celiker, H.; Yildirim, A.; Luleci, C. (My University, 1995)
Growth factors were recently held responsible in the pathogenesis of primary hypertrophic cardiomyopathy (PHCM). It appeared that octreotide (OCT), a long-acting somatostatin analog could effectively inhibit growth factors. With this knowledge, OCT treatment was applied to a 34-year-old patient with HCM subcutaneously for four weeks; 50 ?g three times per day during the first week and 100 ?g twice per day the following three weeks. Patient's functional capacity was class III, there were P pulmonale (in lead II P wave 0.6 mV) and inverted T waves (in leads I, aVL, V5-6) on the ECG; left ventricular posterior wall thickness was 17 mm, interventricular septum thickness was 24 mm, left ventricular mass (LVM) was 342 g by echocardiography. At the end of four weeks' treatment the functional capacity rose to I, P wave amplitude declined to 0.3 mV and T wave was diphasic on the ECG and the thickness of the posterior wall and of the ventricular septum declined to 14 mm and 16 mm, respectively. LVM was 242 g on echocardiography. No side effect was observed during treatment. In conclusion, the dramatic improvement obtained with OCT treatment in a patient with PHCM seems promising.
PRIMER HIPERTROFIK KARDIYOMIYOPATILI BIR OLGUDA OCTREOTIDE TEDAVISI ILE SOL VENTRIKUL KITLESINDE DRAMATIK AZALMA
Keywords: octreotide; adult; article; case report; echocardiography; heart left ventricle mass; human; hypertrophic cardiomyopathy; subcutaneous drug administration